Salicylate‐Functionalized Bismuth Oxido Clusters: Hydrolysis Processes and Microbiological Activity. Issue 25 (18th July 2014) - Schlesinger, Maik; Pathak, Amita; Richter, Sebastian; Sattler, Dominik; Seifert, Andreas; Rüffer, Tobias; Andrews, Philip C.; Schalley, Christoph A.; Lang, Heinrich; Mehring, Michael
Abstract: Hydrolysis of either Bi(HSal 4 Me)3 (A ) or [Bi22 O26 (HSal 4 Me)14 ](B ) in dmso gave the 4‐methylsalicylate‐substituted bismuth oxido cluster [Bi38 O45 (HSal 4 Me)24 (dmso)14 (H2 O)2 ]· 4H2 O (1· 4H2 O), which crystallizes in the triclinic space group P $\bar {1}$ with cell parameters of a = 20.7214(5), b = 20.9654(6), c = 22.2128(6) Å, α = 100.867(2), β = 114.108(2), γ = 107.895(2)° and V = 7815.1(4) Å 3 . The hydrolysis ofA was studied by using 1 H DOSY NMR spectroscopy and electrospray ionization Fourier‐transform ion‐cyclotron‐resonance (ESI‐FTICR) mass spectrometry, both of which showed the formation of several larger species under ambient conditions in the presence of moisture. Furthermore, ESI‐FTICR MS analysis of clusterB showed the formation of mainly Bi23 O26 species, which indicates the partial dissociation of clusterB in solution. In addition, the three different bismuth species containing 1 (A ), 22 (B ) or 38 (1· 4H2 O) bismuth atoms per molecular formula were tested for their microbiological activity against three strains of Helicobacter pylori (251, 26695 and B128). A minimum inhibitory concentration (MIC) of 6.25 μg mL –1 for the mononuclear bismuth complexA was obtained, whereas the bismuth oxido clusterB showed a lower activity with MIC values in the range 25–50.0 μg mL –1 . The activity of1· 4H2 O is comparable to commercial remedies based on antimicrobial bismuth subsalicylate (BSS; 12.5 μg mL –1 ). Abstract : Hydrolysis of either Bi(HSal 4 Me)3 or [Bi22 O26 (HSal 4 Me)14 ] in dmso gave the 4‐methylsalicylate‐substituted bismuth oxido cluster [Bi38 O45 (HSal 4 Me)24 (dmso)14 (H2 O)2 ]· 4H2 O. 1 H DOSY NMR and ESI‐FTICR MS revealed an on‐going growth process to finally give the large cluster. Microbiological activity tests against three strains of H. pylori showed higher activity for smaller bismuth species.